The Influence of Service Quality, Brand Image And Distribution To The Decision To Purchase Palmanco Cooking Oil At PT. Palmanco Inti Sawit Medan: The Influence of Service Quality, Brand Image And Distribution To The Decision To Purchase Palmanco Cooking Oil At PT. Palmanco Inti Sawit Medan - Rosinta Romauli Situmeang; William William; Ricky Maruli; Leonardi Hermawan (Institute of Computer Science (IOCS), 2020)
This research was conducted at PT Palmanco Inti Sawit Medan. The purpose of this study is mexamine and analyze the influence of Service Quality, Brand Image and Distribution on Palmanco Cooking Oil Purchase Decisions at PT Palmanco Inti Sawit Medan. There is a decrease in purchasing decisions caused byService Quality, Brand Image and Distribution. This research approach is based on a quantitative approach. The population in this study amounted to 167 customers and the number of samples in the study were 118 customers. The sampling technique used was random sampling. The test uses a linear regression analysis. The conclusion in this study is that Service Quality, Brand Image and Distribution have a positive and significant effect on Palmanco Cooking Oil Purchase Decisions at PT Palmanco Inti Sawit Medan